2020
DOI: 10.21203/rs.2.22887/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical disparities and determinants of childhood diarrheal illness in Ethiopia: Further Analysis of 2016 Ethiopian Demographic and Health Survey

Abstract: Background: Childhood diarrheal illness is the second leading cause of child mortality in Sub Saharan Africa, including Ethiopia. Studies hypothesized that there are regional variations. Thus, the study aimed to examine the spatial variations and to identify the determinants of childhood diarrhea in Ethiopia. Methods: Data from the 2016 Ethiopia Demographic and Health Survey (EDHS) was analyzed. This nationwide survey involved 10,337 children below 5 years old. The survey was carried out using a two-stage stra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Children aged 36-59 months were 3.17 times more affected by diarrhea than children age less than 12 months. This is consistent with other studies conducted in Amhara region, Gamo Gofa Zone, Sidama Zone, Ethiopia [ 4 , 7 , 29 ], Tanzania [ 31 ], and northern Uganda [ 14 ]. A higher percentage of diarrhea cases have occurred among the highest birth order.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Children aged 36-59 months were 3.17 times more affected by diarrhea than children age less than 12 months. This is consistent with other studies conducted in Amhara region, Gamo Gofa Zone, Sidama Zone, Ethiopia [ 4 , 7 , 29 ], Tanzania [ 31 ], and northern Uganda [ 14 ]. A higher percentage of diarrhea cases have occurred among the highest birth order.…”
Section: Discussionsupporting
confidence: 93%
“…The proportional change in variance for the final full model (model IV) revealed that both individual- and community-level factors accounted for about 67.04% of the variation observed for childhood diarrhea. Similar findings were also found in Tanzania [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…In short, from this graph we understand that child of young mother (<20) and that child of mother age >30 were at higher risk of diarrhea disease, as compared to mothers with age interval (20-29). Previous studies are also consistent with this result that under-five diarrhea disease is spatially correlated with neighboring region (cluster), where high (hot spot) value grouping occurred and another one at the opposite extreme with low (cold spot) values grouping occurred [2].…”
Section: Visualization Of the Effect Of Metrical Covariate And Spatial Effectsupporting
confidence: 84%
“…For example, 2 studies by Messelu et al 20 and Nigatu et al 21 were survey-specific, while the others focused on geographical disparities of childhood diarrhea. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2 studies by Messelu et al 20 and Nigatu et al 21 were survey-specific, while the others focused on geographical disparities of childhood diarrhea. 22,23 Evidence at the national level to identify the contributing factors associated with diarrhea by considering the clustering effects is still limited. Limitation of the previously conducted studies are that none of them used a nationally representative pooled dataset to assess the determinants of childhood diarrhea.…”
Section: Introductionmentioning
confidence: 99%